Eksergi dan energi losses turbin unit 1 PLT Gunung Salak paska re-blading - Widayana, Achriyan (Journal of New Energies and Manufacturing, 2022)
Strategy of maintenance management PT. Indonesia Power to support the reliability of the generating unit is replacing rotor turbine blades, which is commonly referred to as re-blading. There are indications that the transfer of exergy and energy that is not optimal in the rotor turbine Unit 1 of Mount Salak Geothermal Power Plant has resulted in Unit 1 being unable to full load (60 MW) after re-blading. The analysis of exergy flow and energy identification is used to determine the magnitude of exergy and energy losses that occur in the steam turbine system. Based on the data calculations that have been done, the value losses exergy and energy in 2020 is 53.12 MWe and 53.10 MW of the total energy entering the turbine area of 370.3 MW. The accuracy of the data with the data commissioning shows that the energy efficiency value that occurs at this time (after re-blading) has increased by 0.93% with Irreversibility of 52.63 MW. The opportunity for improvement can be done by increasing the efficiency of the ejector, so that the percentage of NCG in the condenser that is sucked by the ejector will increase and result in a better pressure in the condenser (vacuum).